Strategic Management of Islamic Boarding School In Building Student Character - Syafruddin Syafruddin; Muh. Arfah; Endah Andayani; Akhmad Sirojuddin; Erni Yolanda (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe the implementation strategy of the MA CI Islamic Boarding School Management to build the morals of students and its relation to the morals of students who are in the Amanatul Ummah Islamic Boarding School Pacet Mojokerto. The study of this research by the researcher's view of the morals of students now as experienced by this nation, the moral decline has hit almost all life in Indonesia or other words, not only an economic crisis and a crisis of trust but also a moral crisis. This article includes qualitative research using a descriptive qualitative approach. The consideration of using this method is to reveal the reality and actuality of the students' morality from the strategies used at the Amanatul Ummah Islamic Boarding School. In collecting data, the researcher used three methods, namely the interview method, the observation method, and the documentation method. The results of the study obtained an overview of the morals of students and the strategies applied at the Amanatul Ummah Islamic Boarding School, namely istiqomah, the implementation of the night prayer system, book recitation, dawn recitation, and the formation of students' morals with the supervision of students by the management, monitoring of kyai and evaluation of all activities.